Case Report: Rare case of signet ring gastric adenocarcinoma with rectal metastasis - Wan Izzah Wan Jaffar; Guo Hou Loo; Fazarina Mohammed; Deborah Chia Hsin Chew; Guhan Muthkumaran; Nik Ritza Kosai (Frontiers in Oncology)
Gastric cancer remains a leading cause of cancer-related mortality worldwide, with the liver, peritoneum, lungs, and bones being the most common sites of metastasis. Rectal metastasis, also referred to as Schnitzler’s metastasis, is extremely rare and may clinically mimic primary rectal carcinoma, complicating diagnosis and delaying appropriate management. We report a case of a 69-year-old male diagnosed with signet-ring cell gastric adenocarcinoma who presented with symptoms of large bowel obstruction and constitutional decline. Cross-sectional imaging revealed a circumferential rectal mass and gastric wall thickening. Endoscopic biopsies of both gastric and rectal lesions confirmed poorly cohesive adenocarcinoma with signet ring features. Immunohistochemistry supported gastric origin of the rectal tumor. The patient underwent laparoscopic-assisted transverse colostomy for symptomatic relief but the planned gastrojejunostomy was abandoned due to extensive peritoneal involvement. He was treated with palliative chemotherapy (FOLFOX followed by modified de Gramont), achieving only transient radiologic response before clinical deterioration. Subsequent progression to lymphangitic carcinomatosis led to a shift toward best supportive care. This case highlights the diagnostic challenge posed by rectal metastasis from gastric cancer and underscores the aggressive nature and poor chemotherapy responsiveness of signet ring cell carcinoma. Clinicians should maintain high suspicion for secondary rectal lesions in patients with diffuse-type gastric cancer and lower gastrointestinal symptoms. Timely endoscopy, comprehensive histopathologic evaluation, and tailored palliative strategies remain essential to optimizing outcomes in such rare and complex presentations.